Analysis of the deposited carbon during Electron Beam Induced Deposition (EBID) in Scanning Electron Microscope using Secondary Ion Mass Spectrometry (SIMS) - Nur Liana Kamal (Universiti Malaysia Perlis, 2008)
Many experiments on the mechanics of nanostructures require the creation of rigid clamps at specific locations. In this work, electron beam induced deposition (EBID) has been used to deposit carbon films that are similar to those that have recently been used for clamping nanostructures. The film deposition rate was accelerated by placing a paraffin source of hydrocarbon near the area where the EBID deposits were made. High-resolution transmission electron microscopy, electron-energy-loss spectroscopy, Raman spectroscopy, secondary-ionmass spectrometry, and nanoindentation were used to characterize the chemical composition and the mechanics of the carbonaceous deposits.